Learning Bushidō From Abroad: Japanese Reactions To The Last Samurai - Chun, Jayson (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Hollywood, struck by a case of Japan "fever" in the early 21st century, churned out a crop of Japan-oriented films such as Lost in Translation [Coppola 2003], Kill Bill Vol. 2 [Tarantino 2004], Memoirs of a Geisha [Marshall 2005] and Letters from Iwo Jima [Eastwood 2006]. But among all these, The Last Samurai [Zwick 2003] received the most positive Japanese audience reaction. This film, about an ex-Civil War American soldier who takes up arms to fight with the last of the samurai, played to mixed reviews in the U.S. but enjoyed a wildly popular reception in Japan. Judging from Japanese online discussion posts and media articles, many Japanese audiences read the film differently from the American critics. Why and what do these reviews tell us about Japan in the beginning of the 21st century? By being a foreign film, The Last Samurai allowed Japanese audiences to celebrate the nationalist messages taboo in a domestically produced film.